(untitled) (Bangladesh Journal of Botany, 2025)
The present investigation was aimed to screen indigenous plant oils for the management of anthracnose (Colletotrichum musae) in banana. Among the plant oils, the highest radial growth inhibition of C. musae (77.78%) was observed with eucalyptus oil (4%) followed by neem. This study demonstrated maximum reduction of anthracnose incidence in Sobri by neem and sesame (64.44%) and in Chini Champa by eucalyptus and sesame ( 73.73%) compared to control. Maximum reduction of anthracnose severity was achieved in Sobri by neem and black cumin ( 60.15%), and in Chini Champa by sesame, linseed, and eucalyptus ( 56.31%) in comparison to the control. Compared to fruit inoculated with C. musae, neem, black cumin, and eucalyptus increased the fruits’ shelf life by two to three days. Neem resulted lowest total soluble solids ( 9.07 °Brix); eucalyptus gave a maximum reduction of physiological weight loss ( 24.93%). Bangladesh J. Bot. 54(3): 477-482, 2025 (September)